Analisis Hukum Tentang Kedudukan Anak Angkat dalam Kewarisan Menurut Hukum Perdata (Studi Putusan No. 32/Pdt.G/2022/PN Mks) - Resdianto Willem; Nurmiati; Haeriyah (Pledoi Law Jurnal, 2024)
ABSTRACT: A child is a responsibility that gives him respect and value as an individual. Adopting a child is the best option for families who have not yet been blessed with children, from the perspective of a legal state,